Performance analysis of solar stills utilizing phase change materials (PCM): Experimental study on energy and exergy efficiency - Cakmak, Fethi Ahmet; Selimefendigil, Fatih; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2026)
Access to fresh water is a significant problem, especially in arid regions, and it is expected to spread to many parts of the world due to increasing population and climate change. Solar stills offer an environmentally friendly and sustainable solution for fresh water production. The use of phase-change materials with energy storage properties is being widely researched to increase the efficiency of solar stills. Phase-change materials can enable the distillation process to continue at night, increasing efficiency. This study experimentally investigated the efficiency effect of using paraffin as the phase-change material in the base of solar stills. The study was conducted in Soma, Manisa, under seasonal conditions in August 2025. Two experimental sets were set up: one without PCM and one with PCM. The experiment was conducted simultaneously for both distillers on the same day and under the same weather conditions. Distilled water amounts were measured in three segments: daily, nighttime, and total. In hourly measurements, maximum distillation was measured as 0.524 kg/m2.h and 0.509 kg/m2.h for the traditional and PCM models, respectively. At 22:00, it was measured as 2.596 kg/m2 and 2.744 kg/m2 for the traditional and PCM distiller models, respectively. A 5.7% efficiency increase was achieved. In nighttime measurements, 0.132 kg/m2 and 0.236 kg/m2 of water could be distilled in the traditional and PCM models, respectively. A 78.78% efficiency increase was achieved. Total distilled water amounts obtained from the distillers at the end of the 24-h period were measured with precision scales. They were measured as 2.72 kg/m2.day and 2.98 kg/m2.day for the traditional and PCM distiller models, respectively. Despite the decrease in daytime efficiency, total efficiency was increased by 9.24% with PCM due to the increase in fresh water efficiency at night. The instantaneous maximum energy efficiency was calculated as 42.31% in the conventional model, while it was 43.99% in the PCM model. When looking at the instantaneous maximum exergy efficiencies, it was calculated as 3.38% in the conventional distillate model and 2.98% in the PCM model.
Keywords: Solar energy; Water productivity; PCM; Energy storage; Latent heat